Determination of diesel engine performance fueled biodiesel (Rubber seed/palm oil mixture) diesel blend - Adam, I.K. (Universiti Malaysia Pahang, 2015)
In this study the effect of speed, load and blend ratio on the performance of a multicylinder indirect injection diesel engine has been determined. Rubber seed/palm oil mixture at an equal blend ratio (50:50 vol. ) was used for biodiesel production with the motivation of cost reduction and properties enhancement. The oil acid value of 33.4mg KOH/g oil was reduced to 1.42mg KOH/g oil via an esterification process followed by transesterification using a hydrodynamic cavitation reactor. Blends of 5-20 vol. biodiesel to diesel fuel were prepared. A statistical tool, Box-Behnken design (BBD) based on response surface methodology was used to predict and to assess the combined effects of variables (speed, load and blend) on the responses, such as torque, power, brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE). The load was found to be the most influential variable both individually and in combination compared to the speed and blend. A strong effect of speed over the responses was noticed except for torque, whereas its combined effect was insignificant except for BSFC and BTE. No significant contribution was observed for the blend over the response except for torque. Furthermore, the models developed fitted the experimental results of all the responses investigated. Â© 2015 Universiti Malaysia Pahang.